Status of Teachers Working in KGBV in Selected Districts of Madhya Pradesh: An Explorative Study - Dutta, Dr. Neeti (Voices of Teachers and Teacher Educators, 2020)
KGBV schools are meant to promote girls education especially among SC, ST, OBC, minorities and girls belonging to BPL families. There are almost 3600 odd KGBV schools operated by central and state government funded through SSA budget. Teachers a vital component of school system are often not permanently recruited and they have the load of not only carrying usual academic and administrative roles but other work has been assigned like of hostel warden. Studies related to KGBV in other states present a dismal picture. Teachers are underemployed, services conditions are pathetic, no social protection schemes are present, paltry sum of money as salary, employed as daily wage earner etc. Madhya Pradesh is the pioneer state in terms of introduction of contractual teachers’ in education system way back in 1997 through EGS scheme. Presently, it is estimated that almost 26000 teachers working in government schools are contractual teachers. The KGBV scheme is operated in MP since inception of the scheme. In MP state model-III of KGBV is functioning wherein largely teachers are appointed on contractual basis. So, it was necessary to take a stock of teachers working in KGBV residential in Madhya Pradesh. From the present survey of KGBV residential, it was found that teachers are not only contractual but they are getting paltry sum of Rupees 2500 against the sum of Rupees 5000/- as per the revised norms of central government. This sum of rupees 2500 is maximum if it happens to be zero absence from the duty. Normally they are called remedial teachers where such nomenclature is absent in the actual norms. They are not given any kind of appointment letter or any kind of leave, they have no service conditions, and they are at the mercy of SMC/DEO and other local authorities. Even after serving for more than five years or more in many cases, they do not get any kind of experience certificate to show that they are working in the school system. There is nothing called professional training for these teachers. These teachers are regularly taking normal classes often of strength 50 fifty students per class in the name of remedial teaching but majority of them are untrained. There is no difference between untrained and trained teachers in terms of salary and other benefits. So, it is needed that these teachers at least get some respectable salary along with few incentives including certain kind of leaves.